2011
DOI: 10.1021/tx200262d
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of 7-Ethylguanine in Leukocyte DNA from Smokers and Nonsmokers by Liquid Chromatography–Nanoelectrospray-High Resolution Tandem Mass Spectrometry

Abstract: There is considerable evidence for exposure of humans to an unknown ethylating agent, and some studies indicate that cigarette smoking may be one source of this exposure. Therefore, we have developed a liquid chromatography-nanoelectrospray-high resolution tandem mass spectrometry-selected reaction monitoring (LC-NSI-HRMS/MS-SRM) method for the analysis of 7-ethyl-Gua in human leukocyte DNA, a readily available source of DNA. [15N5]7-Ethyl-Gua was used as the internal standard. Leukocyte DNA was isolated and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 19 publications
(47 reference statements)
1
46
0
Order By: Relevance
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve detection limits in the low fmol to amol range (1 per 10 8 –1 per 10 9 nucleotides) as required for our in vivo studies, we employed nanoLC/ESI + -HRMS 3 methodology on an Orbitrap Velos mass spectrometer. We and others have recently reported the use of high resolution mass spectrometry for DNA adduct analysis in complex samples and have shown that it dramatically reduces the matrix background, leading to greatly improved signal to noise ratios [37, 45, 46]. …”
Section: Resultsmentioning
confidence: 99%
“…DNA from human blood samples was isolated using the manufacturer’s protocol for DNA purification from buffy coat (Qiagen, Valencia, CA) [37] with minor modifications [36]. DNA isolation from rat liver was performed using the manufacturer’s protocol for DNA purification from tissue (Qiagen, Valencia, CA).…”
Section: Methodsmentioning
confidence: 99%
“…29 Using that study as a starting point, we increased the sensitivity of the analysis for BPDE- N 2 -dG by 4 to 5 orders of magnitude, allowing the detection of BPDE- N 2 -dG at levels as low as 1 adduct per 10 11 nucleotides (S/N = 2) vs the previously described detection limit of 53 adducts per 10 8 nucleotides (S/N = 6). 29 Some of this improvement in sensitivity can be accounted for by the larger amount of DNA analyzed (~40 μg vs 2 μg), however the majority of the improvement is attributable to several important features which optimized our existing HRAM MS 2 nanospray quantitation methodology 2326 as discussed below, and can potentially be used to improve the sensitivity of other quantitative assays.…”
Section: Resultsmentioning
confidence: 99%
“…88,159,160,163,165 Recently, high-resolution Orbitrap mass spectrometers have been used for the detection of alkylated DNA lesions induced by carcinogens present in tobacco smoke. 344,345 Owing to their accurate mass measurement capability and high sensitivity, we expect more applications of this type of instruments for the quantification of low levels of oxidatively generated DNA lesions in cellular and tissue samples in the future. The improvement in LC-MS-based quantification techniques will also enable systematic adductomics research, 346348 which may facilitate the discovery of novel oxidatively induced DNA lesions involved in the pathogenesis of human diseases.…”
Section: Discussionmentioning
confidence: 99%